Testing the Value Function of the Prospect Theory on Russian M&A Market - Bogatyrev, Semen Y. (Journal of Reviews on Global Economics, 2018)
The article is devoted to the empirical implementation of the prospect theory. The subject is a value function graph. The graph itself was never been plotted on a real empirical data. In this paper a real market situation is considered. Logical indicators which describe and measure the market’s actor’s status and their intensives in different behavioral strategies are proposed. The empirical data from real M&A markets in Russia is collected and a real value function graph is drawn. It is compared to a theoretical value function graph which accompanies the prospect theory. A totally different shape of the curve is noticed. New shape resembles very much the graph of indifference curves, which are well known to the economists back to the late 19th century.